LINGUISTIC AND DIDACTIC PRINCIPLES OF TEACHING THE STATE LANGUAGE IN FOREIGN LANGUAGE MAJORS - Umida Abdurasulova (Innovate Conferences, 2026)
This article presents a scientific and theoretical analysis of the linguistic and didactic principles of teaching the state language—Uzbek—to students majoring in foreign languages. The study substantiates the methodological significance of systematic, communicative, competence-based, and integrative approaches in the process of state language instruction.
Keywords: state language, foreign language, linguistic principles, didactic principles, linguodidactics, competence-based approach, multilingualism, language transfer.